The Influence of GCG on Disclosure of ESG Scores of Companies Listed on the IDX - Marheni, Dewi Khornida; Erick, Erick; Ramadani, Arienda Gitty; Wandi, Yulfis (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
A sustainability report became one of the requirements for corporations to publish as one of the key factors of why the investor wants to invest in the corporation. In Indonesia, there is a regulation for corporations to implement sustainability. Along with good corporate governance, generated a good sustainability report. In Indonesia, approximately about 55% of the companies have published sustainability reports. Hence, this research is purposed to know the influence of good corporate governance in sustainability reports in Indonesia. This research uses a quantitative research design to collect numerical data to test the hypothesis. In this research, 54 companies listed on the IDX that had published sustainability reports for 5 consecutive years were used. In addition, the study collected secondary data from the selected companies' annual, financial, and sustainability news from 2017 to 2021. The results of this research indicate that board independence significantly affects the disclosure of the ESG Scores of companies included in the IDX index. As a result, the board independence of companies in Indonesia is one of the components that help improve ESG Scores' disclosures.